Numerical Simulation of Flame Combustion Characteristics of Tail Gas From the Copper Slag Depleted Reduction - Sun, Huiping; Xie, Haojie; Luo, Siyi; Zhang, Weiwei; Zuo, Zongliang; Xianjun, Guo (Frontiers in Energy Research, 2022)
The tail gas with relatively high calorific value, generated from the depleted reduction of copper slag, can be used as the fuel for gas turbines. In this paper, the flame speed calculation module in PREMIX of CHEMKIN was used to simulate the combustion characteristics of the tail gas after sulfide removal, the effects of equivalence ratio, gas preheating temperature, as well as the CO2 concentration on the flame burning speed were mainly investigated. Results show that the flame propagation velocity increases continuously with the increase of preheating temperature while decreases continuously with the increase of CO2 concentration. Additionally, the peak value of flame propagation velocity appears as the equivalence ratio being 2.0. Compared with the typical methane flame propagation velocity distribution, the gradient of the decreasing phase of flame propagation velocity of tail gas is significantly lower than that of methane flame. However, the maximum value of flame propagation velocity is higher than that of methane flame.